2013
DOI: 10.5423/ppj.si.11.2012.0173
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Quorum Sensing in Acyl-homoserine Lactone-Producing or -Degrading Tobacco Plants Leads to Alteration of Induced Systemic Resistance Elicited by the Rhizobacterium Serratia marcescens 90-166

Abstract: Numerous root-associated bacteria (rhizobacteria) are known to elicit induced systemic resistance (ISR) in plants. Bacterial cell-density-dependent quorum sensing (QS) is thought to be important for ISR. Here, we investigated the role of QS in the ISR elicited by the rhizobacterium, Serratia marcescens strain 90−166, in tobacco. Since S. marcescens 90−166 produces at least three QS signals, QS-mediated ISR in strain 90−166 has been difficult to understand. Therefore, we investigated the ISR capacity of two tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…On the other hand, tobacco plants have been engineered to produce short- and long-side chain AHL-compounds which could be detected in substantial amounts at leaf and root surfaces as well as in soil (Scott et al, 2006 ). Constitutive expression of QS genes in transgenic tobacco plants leads to alteration in induced systemic resistance elicited by the rhizobacterium Serratia marcescens 90–166 (Ryu et al, 2013 ). Furthermore, transgenic tomato plants engineered to produce different AHL-compounds were demonstrated to alter the activity of plant growth promoting rhizobacteria and resulted, e.g., in increased salt tolerance (Barriuso et al, 2008 ).…”
Section: Bacterial Quorum Sensing Molecules Like N mentioning
confidence: 99%
“…On the other hand, tobacco plants have been engineered to produce short- and long-side chain AHL-compounds which could be detected in substantial amounts at leaf and root surfaces as well as in soil (Scott et al, 2006 ). Constitutive expression of QS genes in transgenic tobacco plants leads to alteration in induced systemic resistance elicited by the rhizobacterium Serratia marcescens 90–166 (Ryu et al, 2013 ). Furthermore, transgenic tomato plants engineered to produce different AHL-compounds were demonstrated to alter the activity of plant growth promoting rhizobacteria and resulted, e.g., in increased salt tolerance (Barriuso et al, 2008 ).…”
Section: Bacterial Quorum Sensing Molecules Like N mentioning
confidence: 99%
“…For instance, if SAL-17 produces a wide variety of AHLs and higher IAA than SAL-21 and SAL-12, the response toward SAL-17 single inoculation and a mix inoculation (SAL-17 + SAL-21) was more pronounced on different biochemical, physiological, and growth parameters of wheat. AHLs directly or indirectly induce stress resistance in plants through QS-mediated production of metabolites (Ryu et al, 2013). It has been reported that inoculation of 3-oxo-C12-HSL-producing bacterial strains induce salt stress tolerance, metabolic regulation, and phytohormone response in tomato and Medicago truncatula (Mathesius et al, 2003;Barriuso et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…PGPR producing IAA may enhance the resistance against pathogens. The ISR has already been shown to be effective in rhizobacterium S. marcescens acting as a PGPR (Ryu et al, 2013).…”
Section: Genes Involved In the Plant Growth Promotion Traitsmentioning
confidence: 99%